NOMINAL GROUPS USED IN THE FAIRY TALE “CINDERELLA” FROM THE PERSPECTIVE OF SYSTEMIC FUNCTIONAL GRAMMAR / Pham Thi Ha; NHDKH Ph.D Do Kim Phuong - Pham, Thi Ha
The study deals with the nominal groups in a chosen English fairy tale ‘Cinderella’ in terms of experiential and logical structures and also to see how these groups are used in Vietnamese translation “Cô bé Lọ lem”. This study is descriptive qualitative study. It is kind of method which is conducted by collecting data, analyzing the data, and drawing representative conclusion.